Augmented Reality Game (ARG), 21st century skills and ESL classroom - Karmila Rafiqah M. Rafiq; Harwati Hashim (Journal of Educational and Learning Studies, 2018)
The rapid advancement of technologies is irrefutable with the emergence of the 4th Industrial Revolution. Various industries have employed technologies in aiding their daily tasks, including the educational field. In Malaysia, the Ministry of Education proposed the integration of technology in the classroom. However, with the rising of technologies, graduates lack the soft skills and English language proficiency for the 21st-century jobs. To further curb the problem, Augmented Reality Game (ARG) is recommended for ESL classroom. Thus, this paper aims to identify the 21st-century skills enhanced through ARG and find out the benefits of ARG in English as a Second Language (ESL) learning. Based on the reviews of previous studies, it can be summed up that ARG can enhance the 21st-century skills, which are collaboration, communication, critical thinking and problem solving and at the same time, improves the English language of students. Additionally, motivation and Personal Learning Environment (PLE) are some of the contributing factors for the success of ARG. Therefore, to enhance the 21st-century skills in students, technological tools, such as ARG is deemed to be beneficial.